Odpowiedź :
a) 6x + 12 = 42
6x = 42 - 12
6x = 30
x= 5
b) 40 - 6x = 28
-6x = 28 - 40
-6x = -12
x = 2
c) 3x - 12 - 2x = 1
x - 12 = 1
x = 1 + 12
x = 13
d) 4x - 3-7x =-24
-3x - 3 = -24
-3x = -24 + 3
-3x = -21
x = 7
e) 97=2x-5
-2x = -5 - 97
-2x = -102
x = 51
Odpowiedź:
a) 6x + 12 = 42
6x = 42 - 12
6x = 30
x= 5
b) 40 - 6x = 28
-6x = 28 - 40
-6x = -12
x = 2
c) 3x - 12 - 2x = 1
x - 12 = 1
x = 1 + 12
x = 13
d) 4x - 3-7x =-24
-3x - 3 = -24
-3x = -24 + 3
-3x = -21
x = 7
e) 97=2x-5
-2x = -5 - 97
-2x = -102
x = 51
Szczegółowe wyjaśnienie:
licze na naj